2008
DOI: 10.1074/jbc.m802542200
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the GroEL-GroES Reaction Cycle via the Symmetric Intermediate Implied by Novel Aspects of the GroEL(D398A) Mutant

Abstract: The Escherichia coli chaperonin GroEL is a double-ring chaperone that assists in protein folding with the aid of GroES and ATP. It is believed that GroEL alternates the folding-active rings and that the substrate protein (and GroES) can bind to the open trans-ring only after ATP in the cis-ring is hydrolyzed. However, we found that a substrate protein prebound to the trans-ring remained bound during the first ATP cycle, and this substrate was assisted by GroEL-GroES when the second cycle began. Moreover, a slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 41 publications
2
48
1
Order By: Relevance
“…For example, recent work has suggested that non-native substrate protein can bind to the trans ring of an ATP bullet complex, an observation that conflicts with a central assumption of the standard reaction model (17). Other recent work has suggested that ADP release plays a central role in the reaction cycle (18,19), whereas still other studies have suggested that ATP binds to an open GroEL ring before non-native substrate protein (20).…”
mentioning
confidence: 74%
“…For example, recent work has suggested that non-native substrate protein can bind to the trans ring of an ATP bullet complex, an observation that conflicts with a central assumption of the standard reaction model (17). Other recent work has suggested that ADP release plays a central role in the reaction cycle (18,19), whereas still other studies have suggested that ATP binds to an open GroEL ring before non-native substrate protein (20).…”
mentioning
confidence: 74%
“…Sameshima et al (31) monitored the fluorescence resonance energy transfer between GroEL and GroES and found that nearly equivalent amounts of football and bullet complexes coexist in the mixture during the functional reaction cycle. Koike-Takeshita et al (32) reported that a slow ATPhydrolyzing GroEL mutant can bind substrate protein and GroES at both rings of the GroEL to generate a football complex. These two studies also suggested that the football complex is generated in ATP, and the bullet complex is in ADP.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, mHsp60 assembles into a double-ring structure that binds two mHsp10 molecules, one at each end of the tetradecamer, forming the symmetric chaperonin complex [mHsp60 14-(mHsp10 7 ) 2 complex], previously termed the "football complex." This complex was found to play an important role in the chaperonin protein-folding reaction cycle (34)(35)(36)(37)(38)(39)(40)(41). To distinguish between the two symmetric halves of the football, we called one of the halves the "north pole" and the other the "south pole" (the full nomenclature of subunits is provided in Fig.…”
Section: Significancementioning
confidence: 99%